(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The Islamic financial system is part of the Islamic ecosystem, which includes economic relations in accordance with the rules of Islamic law in the use and distribution of funds.In this article, due to the focus on reforming the financial market in our country, the problems that hinder the introduction and use of Islamic financing and Islamic securities and suggestions for their elimination are given.